Refractive Error and Eye Health: An Umbrella Review of Meta-Analyses - Yin-hao Wang (Frontiers Media S.A., 2021)
Purpose: To explore the associations between refractive errors and multiple eye health outcomes.Methods: This is an umbrella review based on systematic reviews with meta-analyses. In our study, refractive errors included myopia, hyperopia, astigmatism, and anisometropia. We reconducted the meta-analyses whose primary data were available in sufficient detail by random effect model. Heterogeneity was assessed by I2. The main outcomes included myopic macular degeneration (MMD), retinal detachment (RD), cataract, open-angle glaucoma (OAG), strabismus, age-related macular degeneration (AMD), and diabetic retinopathy (DR).Results: Myopia was associated with increased risk of MMD (relative risk = 102.11, 95% CI 52.6–198.22), RD (3.45, 1.08–11.00), nuclear cataract (2.15, 1.53–3.03), posterior subcapsular (PSC) cataract (1.74, 1.41–2.15), OAG (1.95, 1.74–2.19), exotropia (5.23, 2.26–12.09), but decreased risk of DR (0.83, 0.66–1.04), and early AMD (0.80, 0.67–0.94). From mild-to-high myopia, the association strengthened for MMD, RD, nuclear cataract, PSC cataract, OAG, and DR. Hyperopia was associated with an increased risk of early AMD (1.09, 1.01–1.18) and esotropia (22.94, 10.20–51.62). Astigmatism and anisometropia were associated with increased risk of both exotropia and esotropia.Conclusions: Myopia, especially high myopia, demonstrated the highest risk for eye health outcomes, such as MMD, RD, OAG, nuclear and PSC cataracts, and exotropia. However, myopia was associated with a lower risk of early AMD and DR. Individuals with hyperopia are more likely to suffer early AMD and esotropia. Astigmatism and anisometropia predispose to strabismus. A lot of research studies on the mechanism of the associations are needed.Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=239744; identifier: 239744